The cytotoxicity and skin irritation of nanostructured cellulose surface fabricated by a plasma-induced method - Park, Gee Ho; Ko, Tae-Jun; Min, Hye Sook; Kim, Min Sung; Kim, Jung-Ah; Jeon, Byoungjun; Kim, Youngmin; Huang, Yan; Jin, Xian; Wufuer, Maierdanjiang; Oh, Kyu Hwan; Kim, Mi Ok; et al. (SPRINGER, 2019)
Applications of nano-sized cellulose, such as use in tissue bio-scaffolds and drug delivery, have gained much attention in medical research. However, there are only a few studies reporting the skin toxicity of nano-sized cellulose. Here, we investigated the skin toxicity of plasma-induced nanostructured cellulose (PINC) in vitro and in vivo. Morphology of the PINC as well as that of human foreskin fibroblast (Hs27) and immortalized human keratinocyte (HaCaT) cell lines cultured on PINC were analyzed by scanning electron microscopy. The in vitro cytotoxicity of the material was evaluated using Hs27 and HaCaT cell lines and a reconstructed human epidermis model. For in vivo skin toxicity testing, after attaching the PINC to the dorsal skin of Sprague-Dawley rats, skin irritation was evaluated visually and histologically. Our results showed no cytotoxicity of PINC, which did not induce apoptosis or necrosis in either type of cells tested. PINC also did not stimulate irritation on rats in vivo, and no significant inflammatory responses were observed by histological analysis. These results indicate that PINC has no significant skin toxicity in vitro or in vivo. The absence of skin toxicity in PINC suggests that it can be used for skin-related applications without any harm.
Keywords: ANTIBACTERIAL; NANOCRYSTALS; EFFICACY